The Role of Rafiq Chalak in The Development of Kurdish Theater - Shamal Aziz Hamad amin Raswl; Kaify Ahmad Abdulqader (QALAAI ZANIST JOURNAL, 2024)
Every nation has its own genre of theater. The Kurdish nation emerged in the early twentieth century. The content of theatrical texts and plays stem from the lives of individuals in Kurdish society. The title of the research is: (The role of Rafiq Chalak in the development of Kurdish theater), through which we have been able to discuss the efforts and experiences of Rafiq Chalak in the field of writing theatrical texts and playing roles in plays. Rafiq Chalak was not only a good writer of plays, but also an experienced translator. He was able to translate several plays into Kurdish and directed several plays.